2007
DOI: 10.1071/sh07042
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the population-level impact of vaccination on the transmission of human papillomavirus type 16 in Australia

Abstract: Mass vaccination with a highly effective vaccine against HPV 16 has the potential to substantially reduce the incidence and prevalence of infection. Catch-up vaccination offers the potential to substantially reduce the delay before the benefits of vaccination are observed. A booster vaccination might be required to prevent an increase in incidence of infection in women over 25 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 36 publications
2
44
0
1
Order By: Relevance
“…56 Yet other studies have compared scenarios in which naturally acquired immunity is either lifelong or of finite duration (e.g. 57 ), or have allowed the rate at which immunity wanes to vary over a given range (e.g. 50 ).…”
Section: Does Naturally Acquired Infection Confer Immunity To Re-infementioning
confidence: 99%
See 2 more Smart Citations
“…56 Yet other studies have compared scenarios in which naturally acquired immunity is either lifelong or of finite duration (e.g. 57 ), or have allowed the rate at which immunity wanes to vary over a given range (e.g. 50 ).…”
Section: Does Naturally Acquired Infection Confer Immunity To Re-infementioning
confidence: 99%
“…However, as discussed above, data from the clinical trials suggest that transient infections and a small number of persistent infections can occur in vaccinated individuals, 59,60 and these may or may not be transmissible. Regan et al 57 considered transient infection in estimating the impact of an HPV-16 vaccine in Australia, and showed that this has significant implications for herd immunity and overall effectiveness of vaccination. In particular, this modelling demonstrates that the impact of vaccination on reducing incidence and prevalence is reduced significantly if transient breakthrough infection can occur and is transmissible.…”
Section: How Effective Are the Current Vaccines At Preventing Infection?mentioning
confidence: 99%
See 1 more Smart Citation
“…Time is needed to suitably answer this question (WHO, 2006;Olsson et al, 2007) Einstein et al while comparing the immune response and reactogenicity of 2 vaccines by using the same pseudovirion-based neutralisation assay, stated that for any age strata, the positivity rates for the anti-HPV 16 and 18 neutralising antibodies in the cervicovaginal secretions and circulating HPV 16-and 18-specific memory B cell frequencies were higher after vaccination with the bivalent vaccine compared to the quadrivalent vaccine (Einstein et al, 2009). Regan et al (24) considered transient infection in estimating the impact of an HPV 16 vaccine in Australia and showed that it has significant implications on patient immunity and overall vaccine effectiveness (Regan et al, 2007).…”
Section: Do Those Vaccines Activate the Immune Memory System?mentioning
confidence: 99%
“…The first model predicts that vaccination of 80% of 12-year old girls in Australia will eventually reduce HPV type 16 prevalence by 60 to 100% in vaccinated and 7 to 31% in unvaccinated females whereas if 80% of boys are also vaccinated, reductions will be 74 to 100% in vaccinated and 86 to 96% in unvaccinated females. (72) The second model explores the optimal age at vaccination and pattern of vaccine introduction in Finland. (73) The authors find that, once the full impact of vaccination is reached, the annual proportion of HPV type 16-associated cervical cancer cases prevented is expected to be 67% if vaccination of girls occurs at age 15 years, and/or 68% if it occurs at age 12 years, assuming 70% coverage.…”
Section: Contribution Of Male Hpv Infection To Female Infection and Dmentioning
confidence: 99%